Konservasi Lingkungan Melalui Pengembangan Agrowisata Di Desa Wisata Gunungsari, Pamijahan, Bogor, Jawa Barat - Revi Agustin Aisyianita; Saskia Salsabila Rizkiyani; Diva Annisa Damanik; Roro Intan Cici Permatasari (STIE Pariwisata API Yogyakarta, 2025)
This research explores how agritourism development in Gunungsari Tourism Village, Pamijahan District, Bogor Regency can support environmental conservation efforts while highlighting the active role of the local community and the challenges they face. Located in hilly terrain with cool air and fertile agricultural land, Gunungsari Village offers various agricultural commodities such as vegetables, fruits, and attractive natural tourism potential. The community still maintains traditional farming systems and local wisdom in managing their land, creating opportunities to integrate agritourism concepts with environmental conservation approaches. Using a descriptive qualitative approach through field observations, literature studies, identification of agritourism potential, and direct interviews with local communities and village tourism managers, this research aims to contribute to formulating an environmentally friendly tourism village development model based on local potential. The findings can serve as a reference for other tourism villages in Indonesia seeking to balance economic growth with environmental preservation through sustainable tourism practices.